2016
DOI: 10.1017/s1041610216000995
|View full text |Cite
|
Sign up to set email alerts
|

Subtle changes in daily functioning predict conversion from normal to mild cognitive impairment or dementia: an analysis of the NACC database

Abstract: Background There are relatively small but observable changes in functional ability in those without Mild cognitive impairment (MCI) or dementia. The present study seeks to understand whether these individuals go on to develop MCI or dementia by assessing the association between baseline Functional Activities Questionnaire (FAQ) and conversion independent and after adjustment for cognitive tests. Methods The NACC database was used to conduct the analysis of which 7,625 participants were initially identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 79 publications
2
16
1
Order By: Relevance
“…Prior work has shown that a cutoff of ≥6 on the FAQ best discriminated MCI from AD [33]. While this suggests that the change in functional ability captured by the present study may reach the level of dependence on IADLs, previous studies have demonstrated that increased functional difficulty is a significant risk factor for future functional disability and cognitive decline [51][52][53]. Thus, the present findings have implications for the early identification of individuals that are increased risk for functional decline, and they add to a promising body of literature highlighting the utility of employing cardiovascularbased intervention strategies as a method for reducing the prevalence of functional decline due to cognitive impairment in the aging population (see [54] or [55] for a review).…”
Section: Discussionmentioning
confidence: 50%
“…Prior work has shown that a cutoff of ≥6 on the FAQ best discriminated MCI from AD [33]. While this suggests that the change in functional ability captured by the present study may reach the level of dependence on IADLs, previous studies have demonstrated that increased functional difficulty is a significant risk factor for future functional disability and cognitive decline [51][52][53]. Thus, the present findings have implications for the early identification of individuals that are increased risk for functional decline, and they add to a promising body of literature highlighting the utility of employing cardiovascularbased intervention strategies as a method for reducing the prevalence of functional decline due to cognitive impairment in the aging population (see [54] or [55] for a review).…”
Section: Discussionmentioning
confidence: 50%
“…That is, according to current clinical diagnostic criteria, individuals with the exact same cognitive test scores may be diagnosed with either mild dementia or MCI depending on their level of functional ability. Further, it has been shown that even small differences in the FAQ can have a robust threshold effect, such that any increase over 1 point on the FAQ sum is associated with a threefold increased risk of conversion from MCI to dementia (Mis, Devlin, Drabick, & Giovannetti, 2019) and a significantly greater risk of conversion to either MCI or dementia in healthy controls (Nowrangi, Rosenberg, & Leoutsakos, 2016). Therefore, even small effects of informant features, such as the modest effect sizes observed in this study (.008 < η p 2 's ≤ .033), may have a meaningful impact on predictive validity of the FAQ.…”
Section: Discussionmentioning
confidence: 99%
“…Others have attempted to predict Alzheimer’s disease through genomic analysis, brain imaging, and medical record review [ 24 , 25 , 26 ]. Still others have attempted to predict dementia by changing the examination battery for dementia and its biophysical properties [ 27 , 28 , 29 ].…”
Section: Previous Workmentioning
confidence: 99%
“…They performed various neuropsychological tests such as MMSE, CDRsB, FCSRT, Trail Making Test, categorical and lexical verbal fluencies, Instrumental Activities of Daily Living and Geriatric Depression Scale. Nowrangi et al [ 28 ] predicted dementia from data collected from 7625 volunteers at the National Alzheimer Coordinating Center in the United States. They found that behavioral factors, such as filing taxes, remembering dates, and significant travel affected prediction of dementia progression by surveying patients using the Functional Activities Questionnaire (FAQ).…”
Section: Previous Workmentioning
confidence: 99%